Creep of isotropic homogeneous and nonaging of linear-viscoelastic materials under the complex stress state - Pavlyuk, Y. V. (Київський національний університет імені Тараса Шевченка, 2019)
The relaxation of isotropic homogeneous and non-aging linear-viscoelastic materials under conditions of complex stress state is considered. Thin-walled tubular specimens of High Density Polyethylene (HDPE) for creep under a single-axial stretching, with a pure twist and combined load tension and torsion are considered as base experiments, tests. The solution is obtained by generalizing the initial one-dimensional viscoelasticity model to a complex stressed state, constructed using the hypothesis of the proportionality of deviators. The heredity kernels are given by the Rabotnov’s fractional-exponential function. The dependence between the kernels of intensity and volumetric creep is established, which determine the scalar properties of linear viscoelastic materials in the conditions of a complex stressed state in the defining equations of the type of equations of small elastic-plastic deformations, and the kernels of longitudinal and transverse creep defining the hereditary properties of linear-viscoelastic materials under the conditions of the uniaxial tension. The problems of stress relaxation calculation of thin walled tubes under combined tension with torsion have been solved and experimentally approved.Key words: relaxation, linear-viscoelastic, heredity kernel.Pages of the article in the issue: 150-153Language of the article: Ukrainian